Nursing Students Knowledge Regarding Biochemical Changes During Epilepsy : A Cross Sectional study: Pengetahuan Mahasiswa Keperawatan Mengenai Perubahan Biokimia Selama Epilepsi: Studi Potong Lintang - Tadamoun Sabah Yunus (Universitas Muhammadiyah Sidoarjo, 2024)
Background: neurological disorders that impact millions of people globally. Epilepsy, which affects people of all ages and backgrounds, is characterized by frequent, spontaneous seizures. Objectives: This study aims to assess the knowledge of epilepsy among nursing students. And to determine the relationship between nursing student knowledge and socio-demographic features (age, gender, type of study, stage, address, and marital status). Methodology: 150 participants from the University of Basrah's College of Nursing participated in a descriptive cross-sectional study that included morning and evening studies as well as second, third, and fourth stage students. The research began on November 24, 2023, and ended on March 22, 2024. Data was gathered via a questionnaire with closed-ended questions. A panel of nine experts evaluated the instrument (questionnaire) to establish its content validity, and Cronbach's Alpha was used to gauge the questionnaire's reliability. SPSS version 26 was used for the analysis, and the data was presented using the Chi-Square test, frequency, percentage, mean score, and standard deviation. Results: This study showed that (82%) of nursing students had good knowledge regarding epilepsy, (18%) of them had poor knowledge. Students had poor knowledge of life modification for epilepsy (56%). Students had poor knowledge of the definition of status epilepticus (58.67%) female students had better knowledge than male students in which (76%) of them had good knowledge while males had (24%) good knowledge. Conclusion: The current study found that nursing students know epilepsy well Highlights: Analyzed cash flow statements and capital investment reflections. Developed recommendations for reporting capital investments. Examined international practices on long-term asset reporting. Keywords: Nursing Students, Knowledge, Epilepsy